Mannitol improves Monascus pigment biosynthesis with rice bran as a substrate in Monascus purpureus - Chen, Di; Li, Han (Frontiers in Microbiology, 2023)
To reduce the cost of Monascus pigments (MPs) production, the utilization of rice bran (RB), an agricultural waste product, as a substrate in submerged fermentation was conducted in this work. In order to improve MPs production, different nutritional ingredients including mannitol (Man), NH4NO3 (AN), ZnSO4 (Zn), and optimization (Opti), which was synthesis of the three above ones, were added in RB medium, respectively. The yields of MPs, pigment constituents, growth and development of Monascus purpureus M9 were investigated in this study. Man had the maximum color value of 3532 U/g, which was 18.69 folds than that of RB, and reached to 76.65% of rice (Rice) fermentation. Man significantly increased production of two orange pigments, monascorubrin and rubropunctatin, of which the yields were 69.49% and 95.36% of the counterpart of Rice. Biomass and colony diameter of Opti presented the maximum value among different groups. AN and RB induced more asexual spore formation, whereas Opti and Man promoted sexual spore production. Comparative transcriptomic analysis showed different nutritional ingredients led to the changes of pigment production, growth and development of M9 through regulating related gene expression. Man and Opti improved MPs production by regulating the primary metabolisms, including Embden-Meyerhof pathway, pentose phosphate pathway, TCA cycle, fatty acid degradation, fatty acid biosynthesis, amino acids metabolism, and fructose and mannose metabolism to provide the precursors (acetyl-CoA and malonyl-CoA) for MPs biosynthesis. This work offered a low-cost method for increasing MPs production and explained the molecular mechanism of nutritional ingredients for enhancing MPs biosynthesis.